(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the use of phraseologisms in the works of Katherine Mansfield, a key figure of early 20th-century modernist literature. It examines how idiomatic expressions, fixed phrases, and colloquialisms contribute to character development, thematic depth, and narrative realism in Mansfield’s stories. The study focuses on selected works such as “The Garden Party,” “Miss Brill,” and “Bliss,” highlighting the role of phraseologisms in expressing social class, psychological states, and cultural identity. The paper also addresses the challenges phraseological elements pose for translation, emphasizing the need to preserve both semantic meaning and cultural nuance. Overall, this research sheds light on Mansfield’s linguistic artistry and her nuanced portrayal of human nature through phraseological richness.